Strategic Behavior and Underpricing in Uniform Price Auctions - Matti Keloharju; Kjell G. Nyborg; Kristian Rydqvist (Fondazione Eni Enrico Mattei (FEEM), 2003)
We study uniform price auctions using a dataset which includes individual bidders' demand schedules in Finnish Treasury auctions during the period 1992-99. Average underpricing amounts to .041% of face value. Theory suggests that underpricing may result from monopsonistic market power. We develop and test robust implications from this theory and nd that it has little support in the data. For example, bidders' individual demand functions do not respond to increased competition in the manner predicted by the theory. We also present evidence that the Finnish Treasury acts strategically, taking into account the fact that the auctions are part of a repeated game between the Treasury and the primary dealers. Empirically, the main driver behind bidder behavior and underpricing is the volatility of bond returns. Since there is no evidence that bidders are risk averse, this suggests that private information and the winner's curse may play an important role in these auctions.
Keywords: D44; G10; 330; Multiunit auctions; uniform price auctions; treasury auctions; market power; demand functions; underpricing; supply uncertainty; seller behavior; Auktion; Verhaltensökonomik; Schätzung; Finnland